Menopause and its management the physiopathologic foundation - Utian, Wulf Hessel (Department of Paediatrics and Child Health, 2021)
An historical survey of all issues relating to the menopause was considered integral to understanding attitudes and the existing state of knowledge at the time of my planning and designing my initial investigations. While the research literature up to late 1966 was essentially narrative in nature, there were many indirect areas of research that could help define both the level of existing knowledge as well as attitudes and perceptions at that time. Above all, by understanding and documenting a comprehensive historical survey, it became possible to define the pertinent questions that needed answers. Key papers in which I documented the history and summarized the state of the art at that time are references 1-5, 107, 109, and my monograph, “Menopause in Modern Perspective (Appleton, Century, Crofts, New York, 1979). I can best summarize the background to my future studies by quoting from my first published analysis of the literature in 1968.107 The critical review opened with the observation that “most of what is published is based on emotional and philosophical premises; the 'change of life' is an emotional subject not only to women, but to men and doctors.” The purpose of the review was then listed as: “1. To analyse the current thoughts regarding the menopause. 2. To draw attention to the paucity of authoritative research and published data. 3. To serve as an indication for the urgent need for research, particularly into the nature of the menopause and the methods for the relief of menopausal symptoms and disorders; the process of 'ageing' and, in particular, the occurrence of osteoporosis and atherosclerosis in postmenopausal women; and the metabolic and vascular changes following acute hormone withdrawal, e.g. after bilateral oophorectomy in the pre- and postmenopausal female.” The conclusions of that 1968 critical review determined my future career path: “Several questions urgently require answers: 1. Is the climacteric a normal physiologic stage in the life of the human female, or is it a simple result of ovarian failure and oestrogen deficiency? 2. Are the manifestations of ageing directly related to diminution of circulating sex hormones? 3. Can the administration of exogenous oestrogen or other sex hormones prevent the manifestations of ageing? 4. Are the oestrogens at present available for administration equivalent in effect to circulating endogenous oestrogens? 5. Does long-term oestrogen administration result in an increased incidence of breast or uterine carcinoma? 6. Do oestrogens have a direct effect on the psychological state and sense of well-being in the postmenopausal patient? To these ends the development of more precise diagnostic techniques and methods of evaluation is vital.